Empathic market research: The added value of eye tracking data for affective computing UX research - Alexander Hahn; Katharina Klug; Florian Riedmüller (PraxisWISSEN Marketing, 2020)
The use of innovative technology and artificial intelligence (AI) is fundamentally changing the way of gaining and analysing data. Regarding emotion, affective computing aims at automated, real-time-based measurement and recognition of emotions by sensors and learning algorithms. Regarding attention, eye tracking can identify the exact visual triggers which release emotional reactions. This article explains how researchers can use both methods to generate encompassing insights for UX research on user emotions and to identify the according visual trigger points. Therefore, experimental studies are conducted using affective computing and eye tracking methods on two digital use cases. – – Der Einsatz apparativer Technologien und künstlicher Intelligenz verändert zunehmend die Beschaffung und Auswertung von Marktforschungsdaten. Immer häufiger erfasst geeignete Bildanalysesoftware emotionale User-Reaktionen mittels Affective Computing. Die visuelle Aufmerksamkeit von Personen lässt sich durch Eye-TrackingGeräten präzise und unmittelbar nachvollziehen. Dieser Beitrag konzeptualisiert den kombinierten Einsatz der beiden apparativen Messansätze für Emotion und Aufmerksamkeit, um für die User-Experience-Forschung einen deutlichen Mehrwert zu schaffen. Hierfür werden anhand zweier empirischer Studien Vor- und Nachteile der spezifischen Methoden aufgezeigt und eine komplementäre Integration der Methoden vorgeschlagen.
Keywords: 650; Digital Empathy; Affective Computing; Eye Tracking; Emotion Research; Chatbot Communication; UX Design